Texture of Fermented Summer Sausage With Differing pH, Endpoint Temperature, and High Pressure Processing Times - A. M. Stelzleni; Chevise L. Thomas; Harshavardhan Thippareddi; Macc Rigdon; Robert W. McKee (Meat and Muscle Biology, 2020)
The objective was to evaluate the quality and texture of all-beef summer sausages produced with varying degrees of fermentation, endpoint cooking temperatures, and high pressure processing (HPP) hold times. Across 3 replications, sausages were fermented and (Process A) cooked to pH 4.6 and thermally processed to 54.4°C with smokehouse chilling, (Process B) cooked to pH 5.0 and thermally processed to 54.4°C with smokehouse chilling, (Process C) cooked to pH 5.0 and thermally processed to 54.4°C with rapid ice bath chilling, (Process D) cooked to pH 5.0 and thermally processed to 48.9°C with rapid ice bath chilling, and (Process E) cooked to pH 5.0 and thermally processed to 43.3°C with rapid ice bath chilling. After chilling, the sausages were sliced, layered, vacuum packaged, and subjected to HPP at 586 MPa for 0, 1, 150, or 300 s. Post HPP, the sausages were evaluated for objective color (n = 9), lipid oxidation (n = 9), water activity (n = 9), texture profile analysis (TPA; n = 15), sensory analysis (n = 9), and proximate analysis (n = 9). Neither process (combination of pH and endpoint temperature) nor HPP affected lipid oxidation (P = 0.45 and P = 0.69, respectively). Process A resulted in a lighter color (P < 0.01) compared to the other process treatments. Additionally, Process A was less red (P < 0.01) than all other process treatments, and Processes D and E were the reddest (P < 0.01). TPA and trained sensory analysis indicated that, as endpoint temperature increased, so did sample hardness (P < 0.05). Springiness, cohesiveness, and gumminess decreased (P < 0.05) as the endpoint temperature decreased. Although springiness and gumminess increased (P < 0.05) with longer HPP hold times, the panelists were unable to detect differences among samples with longer hold times. The use of HPP at 586 MPa for up to 300 s may be incorporated into manufacturing processes for semidry beef summer sausages with limited impacts on color and texture.